Sickle-cell disease in febrile children living in a rural village of Madagascar and association with malaria and respiratory infections. Issue 1 (December 2016) - Maeder, Muriel; Rabezanahary, Henintsoa; Zafindraibe, Norosoa; Randriatiana, Martin; Rasamoelina, Tahinamandranto; Rakotoarivo, Andry; Vanhems, Philippe; Hoffmann, Jonathan; Bénet, Thomas; Rakoto Andrianarivelo, Mala; Rakoto-Alson, Olivat
Abstract Background In Madagascar, the last study on sickle cell disease (SCD) was done in the early 1980s. The country is known as endemic for malaria and respiratory infections. The main objective of this study was to estimate the prevalence of SCD; the secondary objective was to evaluate its association with malaria and respiratory infections. Methods This is a cross-sectional study which was carried out in a rural village in the south east coast of Madagascar between May 2011 and November 2013. Participants were children aged between 2–59 months presenting with fever measured by axillary temperature ≥37.5 °C at inclusion. Genotyping of haemoglobin S was done by PCR and malaria was diagnosed by Rapid Diagnostic Test. Research for viral and atypical bacterial respiratory pathogens was performed on nasopharyngeal swabs. Uni-and multivariate polytomous logistic regression was done to assess associations between microbiological results and SCD status, with HbAA phenotype as reference. Results A total of 807 children were analysed. Prevalence of SCD among febrile children was 2.4% (95% CI, 1.5–3.7%) and that of SCT was 23.8% (95% CI, 20.9–26.9%). There was no difference in the prevalence of malaria infection according to haemoglobin status (p  = 0.3). Rhinovirus (22.5%), adenovirus (14.1%), and bocavirus (11.6%) were the most common respiratory pathogens detected. After univariate analysis, patients with SCD were more frequently infected by parechovirus (p  = 0.01), while patients with SCT were more prone to RSV A or B infection (p  = 0.01). After multivariate analysis, HbAS phenotype was associated with higher risk of RSV A and B infection compared to HbAA (adjustedOR  = 1.9; 95% CI: 1.2–3.1, p  = 0.009), while HbSS phenotype was associated with higher risk of parechovirus infection (adjustedOR  = 6.0; 95% CI: 1.1–31.3, p  = 0.03) compared to HbAA, independently of age, gender, period per quarter, and the other viruses. Conclusion The prevalence of SCD among under-five children presenting with fever was high in the study population. No association was found between SCT and malaria but few viruses, especially parechovirus, seem to play an important role in the occurrence of pneumoniae among SCD patients.